Strukturyzacja województwa wielkopolskiego jako obszaru badań prasy lokalnej - Kowalczyk, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The author presents the analysis of the current territorial structure of Wielkopolska as a potential research field for studies into the local press market and its trends. The contents of the paper comprise a demographic and territorial description of Wielkopolska, including an analysis of the six sub-regions distinguished on the basis of the European Nomenclature of Territorial Units for Statistics (NUTS). The purpose of the paper is to collect information to support the analysis, generalization and comparative examination of the development of the local press in specific areas, and the general presentation of demographic, territorial, socio-economic and cultural conditions. The composition of local press markets depends on such factors as the size and structure of populations, including the proportions of non-productive population (both pre-, and post-production age groups), population density, the rate of urbanization, economic status and levels of unemployment, income, development of educational, cultural, sporting and recreational facilities, historical transformations, including changes in territorial and administrative affiliation, and local press traditions.